2013
DOI: 10.1186/1471-2458-13-242
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of, attitudes toward, and preventive practices relating to cholera and oral cholera vaccine among urban high-risk groups: findings of a cross-sectional study in Dhaka, Bangladesh

Abstract: BackgroundIn endemic countries such as Bangladesh, consequences of cholera place an enormous financial and social burden on patients and their families. Cholera vaccines not only provide health benefits to susceptible populations but also have effects on the earning capabilities and financial stability of the family. Community-based research and evaluations are necessary to understand perceptions about and practices of the community relating to cholera and oral cholera vaccines. This may help identify the ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
65
8
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 20 publications
19
65
8
12
Order By: Relevance
“…The high anticipated acceptability (97%) and OCV campaign coverage (first dose: 91%; second dose: 85%) observed were similar to evaluations from other OCV campaigns [12, 14, 16, 18, 24, 2933], but higher than previously published coverage estimates from the Maela OCV campaign based on a vaccination registry (first dose: 83%; second dose: 61%) [19]. Although assessing vaccination history from recall may introduce bias [34], we observed similarly high coverage (first dose: 93%; second dose: 84%) among those retaining vaccination cards distributed before the campaign.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The high anticipated acceptability (97%) and OCV campaign coverage (first dose: 91%; second dose: 85%) observed were similar to evaluations from other OCV campaigns [12, 14, 16, 18, 24, 2933], but higher than previously published coverage estimates from the Maela OCV campaign based on a vaccination registry (first dose: 83%; second dose: 61%) [19]. Although assessing vaccination history from recall may introduce bias [34], we observed similarly high coverage (first dose: 93%; second dose: 84%) among those retaining vaccination cards distributed before the campaign.…”
Section: Discussionsupporting
confidence: 77%
“…Several other cross-sectional evaluations conducted at single time points in endemic and epidemic cholera settings have similarly documented varying WaSH KAPs [2426]. The improvements we observed at first follow-up survey after the OCV campaign were similar to that of a KAP evaluation in Haiti conducted before and 3 months after an OCV campaign in 2012, the only other pre- and post-campaign KAP evaluation [27].…”
Section: Discussionsupporting
confidence: 77%
“…This fact was studied in Ghana revealed that mothers' duration of school education is strongly associated with health literacy 8 . The findings of another study done in Bangladesh showed that a low level of education on cholera among risky groups calls for supporting health education activities to increase their knowledge on cholera 9 , another study done on the old people in China revealed that candidates who finished high school or higher had 6, 4, and 3 times bigger odds of possessing adequate health literacy than those who . Unexpectedly, in the present study, the uneducated group was more alert to the fact that antibiotics are of no value in the treatment of common cold and influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Dipika Sur (7)(8)(9)(10) Firdausi Qadri (11)(12) Binod Sah (13 For the OCV stockpile the ICG considers three potential scenarios for the deployment of vaccine: outbreaks, humanitarian emergencies, and high risk settings. As with the process for accessing meningococcal meningitis and YF vaccines, the process for accessing the OCV stockpile will involve submission and circulation of a request to the ICG Secretariat, followed within 48 h by the ICG decision.…”
Section: Presenters (References)mentioning
confidence: 99%